Exchange Rate Management in Advanced Transition Economics - Grubacic, Sanja (2017)
The purpose of my sabbatical leave was to enable me to engage in writing a manuscript on Exchange Rate management in Advanced Transition Economics. This project involved gathering, analyzing, and preparing for publishing the new empirical evidence on behavior of exchange rates in several economies of East and Central Europe. The analysis intended to contribute to a theoretical and empirical literature on the importance of foreign exchange markets and exchange rate management in promoting a country's internal and external balance.
Keywords: dept.eco; faculty_collection; sabbatical_report

Economic nationalism in the history of international economics - Grubacic, Sanja; Schuster, Julian (International Journal of Pluralism and Economics Education, 2018)
This paper examines the sources of economic nationalism by a closer examination of the theory and policy of international trade, originating in the 19th century. We compare and contrast the views of British classical writers, the main proponents of trade liberalism, with the writings of Friedrich List, the main proponent of economic nationalism. The focus is on the distributional implications of trade, and the treatment of the benefits that a poor country may derive from trading with a rich country in 19th century economic thought. We also review the current literature on economic nationalism, and find that alternative perspectives emerge from differing views on the benefits and drawbacks of globalisation. We argue that List's approach remains relevant to understanding contemporary economic nationalism because it highlights a historical context in which the adverse distributional implications of foreign trade are likely to provoke nationalist sentiment. © 2018 Inderscience Enterprises Ltd.
Keywords: Distribution; Economic liberalism; Economic nationalism; Free trade; Globalisation; History; Inequality; International economics; List; Malthus; Protectionism; Ricardo; dept.eco; peer-reviewed

Real exchange rates in advanced transition economies - Grubacic, Sanja; Schuster, Julian (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
The recent evidence from Eastern Europe suggests that one of the major obstacles towards the adoption of euro may lie in the impact that the recession of 2008 exerted on the trajectory of real exchange rates in new member countries (European Commission, 2015). This paper aims to establish and explain the relationship between the external shocks derived from the global financial crisis and recession of 2008 and equilibrium real exchange rate in advanced transition economies of Eastern Europe. The interplay between the external and internal balances is explained by developing an inter-temporal optimizing model of the real exchange rate determination in a small open economy with structural distortions. The results of our model suggest that, in the aftermath of recession, if the Eastern European economies attempt to restore and maintain the balance between the consumption, saving, and investment, the equilibrium real exchange rate will tend to reverse its trajectory from appreciation to depreciation over time in order to encourage a greater production in the future. The equilibrium real exchange rate depreciation in the future may obtain either as a result of an increase in the direct subsidies on investment or as a result of reduced subsidies on the "net-of-investment" income. The deprecation of countries’ real exchange rate, however, may continue to act as an effective constraint against the adoption of euro. © 2015, Institute of Eastern Europe and Central Asia. All rights reserved.
Keywords: Eastern European countries; Real exchange rates; Recession; Subsidies; Transition; dept.eco